The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2174/1389201018666171122121350
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potential and Wound Healing Activity of Biosurfactant Produced by Acinetobacter junii B6

Abstract: • DPPH and FRAP assays showed notable scavenging activity. • MDA, H2O2, and GSH; confirmed the scavenging property of the derived biosurfactant through ROS. • Synthesized formula encourages the healing of the wound because of its antioxidant capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…Ohadi et al . () in their study of wound healing in rats showed that the LP produced by Acinetobacter junii B6 increased free‐radical scavenging activities and improved histopathological remission. Lydon et al .…”
Section: Health‐related Applicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Ohadi et al . () in their study of wound healing in rats showed that the LP produced by Acinetobacter junii B6 increased free‐radical scavenging activities and improved histopathological remission. Lydon et al .…”
Section: Health‐related Applicationsmentioning
confidence: 96%
“…It has been suggested that the wound healing properties exhibited by those LPs investigated may be as a result of their ability to reduce oxidative stress through the prevention of reactive oxygen species production. Ohadi et al (2017) in their study of wound healing in rats showed that the LP produced by Acinetobacter junii B6 increased free-radical scavenging activities and improved histopathological remission. Lydon et al (2017) tested a highly purified preparation of micelleforming nonacetylated acidic SL that contained 90% C18 congener suggesting that acidic SLs can be used as a component of antimicrobial creams to reduce the risk of wound infection during healing.…”
Section: Applications In Wound Healingmentioning
confidence: 99%
“…83 Several studies evaluated the potency of different antioxidant agents from herbal and bacterial resources as well as chemically produced ones for elevating the healing rate of chronic wounds. 84 Considering the great effect of antioxidant agents in healing of wound, the healing activity of entrapped Se NPs and VE into PCL/GEL scaffolds as materials with high antioxidant capacity was evaluated in the present study. According to Figure 10(a), the MDA level of tissues treated with PCL/GEL/Se NPs (0.078 µM/mg protein, p-value ≤ 0.01) and PCL/GEL/Se NPs/VE (0.059 µM/mg protein, p-value ≤ 0.001) was significantly lower than negative control (0.13 µM/mg protein).…”
Section: Resultsmentioning
confidence: 99%
“…The FRAP values were expressed as micromoles per liter (µM) and a standard curve that showed millimole Fe 2+ to absorbance was used to read these values. 28…”
Section: Total Antioxidant Capacity Assaymentioning
confidence: 99%